Pontoniine shrimps from the 2003 NORFANZ Expedition, 10 May–16 June (Crustacea: Decapoda: Palaemonidae) - Bruce, A. J. (Zootaxa, 2005)
A report is presented on a small collection of pontoniine shrimps, from the Tasman Sea, by the 2003 NORFANZ Expedition. The report includes information on 5 taxa, including two species new to science, Periclimenes fenneri and P. tangeroa. Hamiger novaezealandiae Borradaile is now recorded for the first time since 1910.